Eco-efficient rendering mortars : use of recycled materials - Farinha, Catarina (Woodhead Publishing series in civil and structural engineering., 2021)
Eco-Efficient Rendering Mortars: Use of Recycled Materials focuses on the use of waste materials into cement-based renders, discussing the origins, treatment processes and properties of relevant wastes. The book dispels mistrust through demonstrating the technical feasibility and environmental benefits of eco-efficient rendering mortars. It considers the characteristics of different waste products, such as aggregates, fillers, binders and additions. The functional requirements of renders are also discussed alongside their impact. Finally, the title considers the lifecycle and durability of modified mortars. This book offers robust support and clear guidance on the use of wastes as a substitute for natural aggregates and binders.